Revolutionizing Marketing: Unleashing the Power of Recycled Product Materials - Nisa, Tasya Ainun (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Increasing awareness of environmental issues has led to changes in the way consumers behave in their life activities. Not only pay attention in terms of health but also in terms of sustainability. This study aims to determine the determination of marketing strategies through recyclable packaging product materials. This research method used is qualitative method. The statistical tools used are Strengths, Opportunities, Aspirations, Results analysis. the total number of informants is 6 people consisting of 2 internal parties of PT. Amcor Flexibles Indonesia and 4 from the customer's side. The analysis techniques used in this study are, Data Reduction, Data Presentation and Conclusion. The results of data analysis showed, PT. Amcor Flexibles Indonesia uses a market penetration strategy by doing better marketing starting from marketing through social media, endorsements from people who have many followers and creating interesting content that can attract many customers.